2020
DOI: 10.2337/dc20-0553
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Associations of NT-proBNP With Risks of Diabetes and Diabetes-Related Complications

Abstract: Circulating N-terminal pro B-type natriuretic peptide (NT-proBNP) is a classic diagnostic and prognostic marker for heart failure. However, it is inversely associated with diabetes risk. We aimed to investigate relationships of NT-proBNP with risk of diabetes-related complications in initially healthy individuals. RESEARCH DESIGN AND METHODSWe performed a case-cohort study within the European Prospective Investigation Into Cancer and Nutrition (EPIC)-Potsdam cohort including a random subcohort (n 5 1,294) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 42 publications
3
16
0
Order By: Relevance
“…Fetuin-A correlated weakly directly with HDL-cholesterol (r = 0.14), non-HDL cholesterol (r = 0.08) and HbA 1c (r = 0.10), and BMI/waist circumference (r = 0.08), and inversely with physical activity (r = -0.12), after adjustment for age and sex, Additional file 1 : Table S1. Participants who developed vascular complications of diabetes were on average older, more likely to be men and had a more unfavorable cardiometabolic profile characterized by higher triglycerides, lower HDL-cholesterol and lower adiponectin [ 33 ]. The median follow-up time (IQR) from diabetes diagnosis on was 12.8 (10.5–15.1) years for microvascular complications and 13.4 (10.9–15.6) years for macrovascular complications.…”
Section: Resultsmentioning
confidence: 99%
“…Fetuin-A correlated weakly directly with HDL-cholesterol (r = 0.14), non-HDL cholesterol (r = 0.08) and HbA 1c (r = 0.10), and BMI/waist circumference (r = 0.08), and inversely with physical activity (r = -0.12), after adjustment for age and sex, Additional file 1 : Table S1. Participants who developed vascular complications of diabetes were on average older, more likely to be men and had a more unfavorable cardiometabolic profile characterized by higher triglycerides, lower HDL-cholesterol and lower adiponectin [ 33 ]. The median follow-up time (IQR) from diabetes diagnosis on was 12.8 (10.5–15.1) years for microvascular complications and 13.4 (10.9–15.6) years for macrovascular complications.…”
Section: Resultsmentioning
confidence: 99%
“…There are large differences in the length of hospital stay of very preterm infants among different regions ( 6 ). In general, infants with necrotizing enterocolitis (NEC), bronchopulmonary dysplasia (BPD), and nosocomial infection have a longer length of stay in the hospital ( 7 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…This can be done through the identification of additional biomarkers that provide incremental prognostic value beyond the SYNTAX II score. Recently, increasing evidence has suggested that NT-proBNP, an established biomarker for the diagnosis and prognosis of heart failure, is associated with the risk of incident diabetes (27,28) and diabetes-related microvascular and macrovascular complications (29). Moreover, higher NT-proBNP levels are associated with an increased risk of death and cardiovascular events in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated NT-proBNP levels reflect the accumulation of cardiovascular risk factors. NT-proBNP has been correlated with macro-and microvascular complications (29), such as MI, stroke, peripheral arterial disease, and diabetesrelated nephropathy, retinopathy, and neuropathy, which all lead to poor cardiovascular outcomes. However, the exact mechanism in diabetic patients with MVD needs to be further elucidated.…”
Section: Discussionmentioning
confidence: 99%